Do Iraqi Ceo Depending On Strategic Planning In The Face Of Crises - Riyadh Hussein Obyes; Zainab Obaidsh Chalab Alkhfaji; Alaa Hussein Fadhil; Ahmed Abdullah Amanah (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The goal of this article is to find the CEO of Iraqi companies that use strategic planning and determine if they are capable of diagnosing the traits of strategic planning systems that improve these companies' capacity to successfully address crisis-related needs. The capacity of the company to successfully react to crisis needs and demands is enhanced by the use of strategic planning, according to a review of data from 64 enterprises utilizing statistical analysis. Furthermore, top and division or unit managers must be involved and committed for strategic planning to be successful. It also has to be planned with an external orientation and get more than just lip service from top and unit or division level managers. In other words, it must concentrate on how well the business responds to the needs of its crisis and it must recognize and take advantage of any future growth crises. Additionally, a CEO must possess a variety of qualities to engage in good strategic planning. Core Competence Knowledge, Skills, and Abilities are especially important for individuals who will be in charge of carrying out the final plan since it must be compatible with the crisis-management and decision-making approaches. The study's findings suggest that managers of Iraqi businesses should think carefully about the value of strategic planning during times of crisis. also Many CEOs lack knowledge, skills, and talents since they did not complete business universities or practical training programs. Managers must attempt to incorporate crisis management into the strategic planning process for their organizations. The conclusion encourages a firm's strategy approach to include crisis management procedures. This contributes to better performance and increased crisis management efficacy. Additionally, the board of directors must rely on advice from experts who can assist them strategize and prepare throughout a crisis, which improves their capacity to handle one effectively. One way to integrate and improve managers' ability to handle crises is to encourage the use of strategic crisis planning.